Architectures of Weaving: From Fibers and Yarns to Scaffolds and Skins - Sauer, Christiane; Stoll, Mareike; Fransén Waldhör, Ebba; Schneider, Maxie (Jovis Verlag GmbH, 2023)
Architectures of Weaving bridges architecture and textile by exploring fiber architectures from the micro scale of biological systems to the macro scale of textile and built structures.Selected case studies, essays, and interviews reflect on cultural practices and materials research through the lens of textile thinking.